THE ROLE OF BUSINESS ORGANIZATIONS IN ACHIEVING COMPETITIVE ADVANTAGE AND ITS IMPACT ON STRATEGIC MANAGEMENT. AN ANALYTICAL STUDY OF IRAQI PUBLIC UNIVERSITIES (World Economics and Finance Bulletin, 2022)
The study aimed at the role of business organizations in achieving competitive advantage and its impact on strategic management through an analytical study of Iraqi public universities. To achieve the objectives of the study, a questionnaire was prepared and distributed (387) to the employees of public universities in Iraq. The study found that there is an impact of the cost dimension on business organizations in strategic management from the perspective of members of Iraqi public universities, and there is an impact of the quality dimension in business organizations on strategic management from the point of view of employees in Iraqi public universities, There is an impact of flexibility in business organizations on strategic management from the point of view of employees of Iraqi public universities & There is a post-handover effect on business organizations in strategic management from the perspective of Iraqi public universities employees